In vitro response of dental pulp stem cells in 3D scaffolds: a regenerative bone material (2018)
Three-dimensional-porous scaffolds of bone graft substitutes play a critical role in both cell targeting and transplantation strategies. These scaffolds provide surfaces that facilitate the response of stem cells related to attachment, survival, migration, proliferation, and differentiation.